Pentamethylphenyl (Ph*) and related derivatives as useful acyl protecting groups for organic synthesis: a preliminary study - Cheong, CB; Frost, JR; Donohoe, TJ (Thieme Gruppe, 2020)
A study of acyl protecting groups derived from the Ph* motif is reported. While initial studies indicated that a variety of functional groups were not compatible with the Br2-mediated cleavage conditions required to release the Ph* group, strategies involving the use of different reagents or a modification of Ph* itself (Ph*OH) were investigated to solve this problem.